Patient Room Controlled By Sensors in the Home - Ali Hayder Qasim Al- Naser; Ali Mahmood Hussein; Muntadher Imad Abdulridha; Shukr Mahmoud Kamaneh; Asmaeel Saeed Etshan (American Journal of Biodiversity, 2025)
The aim of this study is to design and implement a wireless intraoral dental camera that could help the dentist to get a clear view for the oral cavity and aid in the diagnosis of the cases and treatment plans. Tremendous advancement in information technology has completely changed the portals of communication between health care personnel and patients. Newer techniques and advancements used to diagnose diseases remotely in real-time and simultaneously seek expert consultations and advice regarding the treatment protocols for various conditions using established telemedicine platforms are now available. In this review, we aim to discuss the various clinical applications of IOC and its possible impact on patient compliance for dental care. It can be concluded that IOC has diverse applications in oral health care and can effectively assist dentist, dental hygienists, and oral health care providers. Also, the compliance of the patient can be increased by the use of IOCs in diagnosis, treatment planning, goal setting, oral hygiene instructions, and maintenance. However, studies are scant in this area, and a precise understanding of the mechanisms of IOC by which patient compliance can be increased is not very clear for many other potential applications.